A Market Penetration Strategy Framework for New Pharmaceutical Products in Highly Regulated African Healthcare Markets - Michael Aduojo Amuta; Muridzo Muonde; Ashiata Yetunde Mustapha; Akachukwu Obianuju Mbata (International Journal of Scientific Research in Civil Engineering, 2021)
This paper develops a literature-based framework guiding pharmaceutical firms’ market penetration strategies in highly regulated African healthcare markets. Africa’s pharmaceutical market, projected to grow from around USD 30 billion in 2020 to USD 70 billion by 2030, offers significant opportunities but faces formidable regulatory, infrastructural, and policy-related barriers. Building on theoretical foundations Porter’s Five Forces, Rogers’s Diffusion of Innovation, PESTEL, and the Triple-A strategy this study synthesizes secondary sources (peer-reviewed articles, policy reports, regulatory databases) to propose a multi-stage penetration model. The framework integrates regulatory intelligence, stakeholder engagement, entry modes, pricing strategies, and health-system integration. Implications are discussed for pharmaceutical firms, regulators, donors, and patients, with a call for future empirical validation via case studies or pilot implementations
Keywords: pharmaceuticals; market penetration; African healthcare; regulatory strategy; drug access; policy barriers